The whispering skull / 2. - Stroud, Jonathan (Lockwood & Co, 2014)
"Lockwood & Co. are hired to investigate Edmund Bickerstaff, a Victorian doctor who reportedly tried to communicate with the dead, while Lucy is distracted by urgent whispers coming from the skull in a ghost jar"--Provided by publisher.